Metal organic framework UiO-66 and activated carbon composite sorbent for the concurrent adsorption of cationic and anionic metals. (January 2020) - Solis, Kurt Louis B.; Kwon, Young-Hwan; Kim, Moon-Hyeon; An, Ha-Rim; Jeon, Cheolho; Hong, Yongseok
Abstract: A composite sorbent for the simultaneous removal of both Hg 2+ and SeO3 2− from aqueous media was produced from the solvothermal synthesis of a zirconium metal organic framework, UiO-66, in the presence of activated carbon. The composite sorbent has a large surface area of 1051 m 2 g −1 with crystalized porous structures and has strong thermal stability up to 600 °C. The contaminant uptake of the sorbent follows a Langmuir adsorption isotherm with maximum sorption capacity of 205 mg g −1 and 168 mg g −1 for Hg 2+ and SeO3 2−, respectively. Scanning electron microscopy-energy dispersive spectroscopy results show that the Se regions overlap exclusively with Zr-rich regions suggesting that SeO3 2− adsorption depends entirely on the exposed UiO-66 surface. In addition, X-ray photoelectron spectroscopy spectra of Se 3d and Hg 4f showed the association of SeO3 2− and Hg 2+ on the UiO-66 and carbon surfaces, respectively. The sorbent could facilitate the development of a single process for the simultaneous removal of cationic Hg and anionic Se as well as other similar ionic metals with opposite charges from aqueous media. Graphical abstract: Image 1 Highlights: A UiO-66 and activated carbon composite sorbent is synthesized and characterized. Adsorption experiments indicates that the sorbent removes dissolved Hg 2+ and SeO3 2- effectively. Langmuir isotherm best describes the adsorption of Hg 2+ and SeO3 2- to the composite sorbent. The adsorption of SeO3 2- is localized to UiO-66 while Hg 2+ adsorption is not site specific.